SYMBOLIC MUSICAL RESYNTHESIS AS AN EKPHRASTIC COMPOSITIONAL PRACTICE USING COMPUTATIONAL METHODS - Vassallo, Juan (Culture Crossroads, 2023)
In my artistic work, I explore the affordances of computational methods from the discipline of artificial intelligence for music composition. Grounded in philosophical perspectives that revolve around the notions of trans- and post-humanism and cybernetics, I understand the mediating role of computers in music composition as having the potential to expand a composer’s creative process by providing him with novel ways of exploring relationships between musical material and structure. Under this premise, music composition becomes a process that occurs through the assemblage between human actors and technological artifacts, and this association should result in new, interesting, and valuable artistic works. In this text, I will discuss a personal compositional practice that I understand as ekphrastic, based on the notion of symbolic resynthesis of musical symbolic information employing computational methods, as means for composing an original piece in response to the madrigal “Io Mi Son Giovinetta” by Claudio Monteverdi.